Towards an Institutionalist Political Economy - Р Буайе; Э Бруссо; А , Кайе (Journal of Economic Sociology, 2010)
This is a manifest written by Alain Caille on the basis of the lecture series delivered in 2005 in Indonesia by the leading representatives of the non-orthodox French schools of economic thoughts.  Initially the text was written in English. Later on in 2007 they published a French version in La Revue du MAUSS. Soon the Spanish translation appeared. Other famous non-orthodox economists and economic sociologists joined this group of authors (RobertBoyer, EricBrousseau,Alain Caillé, Oliver Favereau), who signed the document.